PENGARUH PROMOTION MIX TERHADAP KEPUTUSAN BERKUNJUNG DI ALAM IMAJINASI TAMAN BUNGA NUSANTARA (Survei terhadap Pengambil Keputusan Rombongan Wisatawan Nusantara Untuk Berkunjung Ke Alam Imajinasi Taman Bunga Nusantara Kabupaten Cianjur) - Putri, Ayunda Purwanti; Novalita, Dewi Pancawati (Universitas Pendidikan Indonesia, 2011)
Kabupaten Cianjur is one of regencies in West java has tourism potential can be relied, and the one of destination is Alam Imajinasi Taman Bunga Nusantara. Alam Imajinasi Taman Bunga Nusantara is a recreation area that offers a variety of tourist attraction with the unique feel for the tourist. The number of tourist visits on Alam Imajiansi Taman Bunga Nusantara has decreased from 2005 to 2009. The most drastic decrease of tourist visit happened in 2009 till 65%. Promotion mix is one of marketing strategy that can be used to increase the number of visit. In connection with these to research studies conducted on the influence promotion mix toward visitin decision Alam Imajinasi Taman Bunga Nusantara. The purpose of this research is to find promotion mix influence visiting decisions to Alam Imajinasi Taman Bunga Nusantara. Promotion mix consists of direct marketing, sales promotion, advertising, interactive/internet marketing, and public relations. Technique of sampling is systematic random sampling. The method in that used in this research is explanatory survey by using ordinal scale. Analyze from this research use Path Analysis with a computer software tools SPSS 18.0. The result of this research is promotion mix influence significantly 86,3% and the rest influence other factors. Based on the result of statistical test results were obtained, there were four variables of promotion mix which had an influence on visiting decisions of direct marketing, sales promotion, interactive/internet marketing, and public relations and there was one variables that had no effect on visiting decisions was advertising.That it can be concluded that direct marketing, sales promotion, interactive/internet marketing, and public relations strong influence the visiting decision on Alam Imajinasi Taman Bunga Nusantara.